Nieustraszeni pogromcy wampirów Romana Polańskiego wobec literackich i filmowych antenatów w kontekście koncepcji estetycznych Romana Ingardena - Rawski, Jakub (Przestrzenie Teorii, 2024)
The aim of the article is to analyze the correlation between Roman Polański’s The Fearless Vampire Killers and literary and film representations of the vampire. Reminiscences of classic works related to the undead, such as Lenora by Gottfried August Bürger, The Vampyre by John Polidori or Dracula by Bram Stoker, as well as cinematic works Dracula by Tod Browning, horror films by Hammer are noticeable in the image. The article attempts to analyze these literary and film threads, using the aesthetic concepts of Roman Ingarden. The categories used in the analysis of the literary-film border of The Fearless Vampire Killers concern: multi-layered structure, underdetermined places, concretization and metaphysical qualities.